Biomass and coal fly ash as cement replacement on mortar properties - Teixeira, Elisabete Rodrigues (2016)
Nowadays, construction sector tries to implement several options to solve the issues related to concrete. The main goal of this work was to study the effect of biomass fly ash, blended with coal fly ashes or alone, as cement replacement in the mortars properties. Mortars with biomass fly ashes have lower slump value than the reference. Mortars with 20% of cement substitution presents better results for all curing time. However, in the three percentages of substitution, and for all curing periods, the best results were found for mortars composed with biomass fly ashes. This work showed that is possible to use biomass fly ashes as partial cement substituent with good results in terms of durability and quality of concrete. Its utilization at an industrial level of concrete production can decrease the energy and raw materials consumption related to cement production and allows a more sustainable option on the ash management.